Oleanolic Acid Cubic Liquid Crystal Nanoparticle-Based Thermosensitive Gel Attenuates Depression Symptoms in Chronic Unpredictable Mild Stress Rats - Shi Z; Wang Q; Li Q; Jia F; Xu W (Drug Design, Development and Therapy)
Zhiqi Shi,1,2,* Qing Wang,1,* Qing Li,1,3 Fan Jia,1,3 Weifeng Xu1 1Wuxi Affiliated Hospital of Nanjing University of Chinese Medicine, Wuxi, Jiangsu, People’s Republic of China; 2Liangxi District Hospital of Traditional Chinese Medicine, Wuxi, Jiangsu, People’s Republic of China; 3Wuxi Institute of Traditional Chinese Medicine, Wuxi, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiqi Shi, Chinese Medicine Research Department, Wuxi, Jiangsu, 214071, People’s Republic of China, Tel +86 510-82725693, Email shi_mars@foxmail.com Weifeng Xu, Drug Clinical Trial Facility Office, Wuxi, Jiangsu, 214071, People’s Republic of China, Tel +86 510-82725693, Email 13585028501@163.comPurpose: Major depressive disorder (MDD) is a global health concern. Studies have demonstrated that oleanolic acid (OA) has a regulatory effect on MDD. However, OA is poorly soluble, has low oral bioavailability, and faces challenges in crossing the blood-brain barrier. In this study, building upon a previous formulation of OA cubic liquid crystal nanoparticles (OA-LCNP), we combined nanoparticles with a thermosensitive gel for nasal administration and investigated the pharmacological effects of OA-LCNP thermosensitive gel (OANG) on depression. This study aimed to evaluate the effects of OANG on depression symptoms in rats.Methods: OANG was prepared using Poloxamer F127 and F68 as the gel matrix, and the ratios of F127 and F68 were investigated. The pharmacokinetics of OANG was studied in rats, and OA content was determined using liquid chromatography-mass spectrometry (LC-MS). The pharmacological effects of OANG on depression were evaluated in chronic unpredictable mild stress (CUMS) model rats.Results: The phase transition temperature of the gel was 34°C, and the release of OA from OANG was slow according to the Higuchi kinetic equation. The AUC0-t of brain tissue after nasal OANG administration was 1.21 times that observed after intravenous administration. Additionally, the brain-targeting efficiency and nasal-brain direct transfer were 29.91% and 9.44% higher, respectively, than those observed after intravenous administration, indicating the brain-targeting capability of the OANG delivery system. Network pharmacological analysis revealed that the anti-depressant effects may be linked to neuroactive ligand-receptor interactions, the PPAR signaling pathway, and efferocytosis signaling pathways. Experimental results from CUMS rats showed that the gel significantly affected interleukin (IL)-4, IL-6, acetylcholinesterase, acetylcholine, 5-hydroxytryptamine, and brain-derived neurotrophic factor, and improved depression-like behavior in rats, as measured by sucrose preference, forced swimming, and box shuttle tests.Conclusion: The OANG nasal drug delivery system has specific brain-targeting properties and exerts anti-depressant effects.Keywords: oleanolic acid, cubic liquid crystal nanoparticles, drug delivery systems, major depressive disorder, chronic unpredictable mild stress